2021
DOI: 10.18332/tid/143179
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tobacco price and taxation on affordability and consumption of tobacco products in the South-East Asia Region: A systematic review

Abstract: INTRODUCTION The objective of the review was to study the impact of tobacco taxes or prices on affordability and/or consumption of tobacco products in WHO South-East Asia Region (SEAR) countries, overall and by socioeconomic status; and change in consumption of one tobacco product for a given change in price/tax on another tobacco product. METHODS The searches were made in five databases (Medline, Embase, Cinahl, EconLit, Tobacconomics) using keywords such as 'tobacco', 'tax', 'price', 'impact' with their syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…5 Previous studies have examined the effects of each cigarette tax component on cigarette smoking. Higher cigarette prices have been shown to decrease overall tobacco consumption, [6][7][8][9][10] cause…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Previous studies have examined the effects of each cigarette tax component on cigarette smoking. Higher cigarette prices have been shown to decrease overall tobacco consumption, [6][7][8][9][10] cause…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined the effects of each cigarette tax component on cigarette smoking. Higher cigarette prices have been shown to decrease overall tobacco consumption,6–10 cause current smokers to quit11–14 and prevent young people from starting smoking 8 15–17. Similarly, studies have shown that as cigarettes become less affordable, consumption decreases 9 18–20.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers found that although some WHO South-East Asia Region (SEAR) countries have sought to raise the price of tobacco products, their tobacco control policies have not kept pace with rapid economic growth. Consequently, to reduce the affordability and consumption of tobacco products, it is important to increase taxes on tobacco products and raise their prices sufficiently to outweigh the effects of income growth 16 . Only when recognizing the high economic burden incurred by smoking do smokers quit in order to enjoy better health and more disposable income 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews that examined the impact of price or tax on tobacco typically focused solely on high-income countries [ 20 22 ] or pointed to a dearth of studies that used data from LMICs [ 23 ]. A 2021 review of south-eastern Asian countries included only five studies that had examined socioeconomic differences in price responsive, and only one published after 2010 [ 24 ]. Similarly, a 2015 review of Latin America and the Caribbean countries identified a single study that had reported price effects by SES categories [ 6 ].…”
Section: Introductionmentioning
confidence: 99%